The December 2018 eruption at Etna volcano: a geochemical study on melt and fluid inclusions - Correale, Alessandra; Corsaro, Rosa Anna; Miraglia, Lucia; Paonita, Antonio; Rotolo, Silvio G. (Frontiers in Earth Science, 2024)
This study focus on the Mt Etna December 2018 eruption with the aim of investigating the geochemical characteristics of the feeding magma. New data on major and trace element geochemistry of olivine-hosted melt inclusions (MI) in volcanic products are presented together with the noble gas geochemistry of fluid inclusions (FI) in olivines. The noble gas geochemistry of fluid inclusions (FIs) in olivines was also investigated. The major element composition of MIs is variable from tephrite/trachybasalt to phonotephrite/basaltic trachyandesite, with SiO2 = 45.51–52.72 wt%, MgO = 4.01–6.02 wt%, and CaO/Al2O3 = 0.34–0.72. Trace element patterns of MIs present a typical enrichment in LILE and LREE, depletion in HFSE, and relatively fractionated REE patterns: (La/Lu) N= 18.8–41.08, with Eu/Eu* = (0.5–1.8). Positive anomalies in Sr (Sr/Sr* = 0.8–2.3) and Ba can be ascribed to the assimilation of plagioclase-rich cumulates in the magmatic reservoir. The variable Ba/La (9.8–15.8), K/Nb (260–1037), Ce/Nb (1.9–3.4), Rb/La (0.4–1.6), and Ba/Nb (10.8–25.8) ratios reveal mixing between two types of end-member magmas comparable to those emitted from 1) the 2001 Upper Vents and 2002–03 Northern Fissures (Type-1) and 2) the 2001 Lower Vents and 2002–03 Southern Fissures (Type-2), respectively. Type-2 represents a magma that was under the influence of a crustal component, whereas Type-1 is compatible with a HIMU–MORB-type heterogeneous mantle source. It appears that the 2018 MIs have captured the two different types of magmas, and the lack of homogenization may imply a very fast ascent (a few months). Compatible with the contemporary presence of primordial HIMU–MORB and crust-contaminated end-members are the data on noble gases from FI that highlighted an 3He/4He value of 6.5–6.6Ra. The hypothesis of two different types of magmas, identified by the trace element geochemistry in MIs, is, thus, reinforced by helium isotopic data on FI of the 2018 eruption together with data from other Etnean eruptions and allows the inference of a bicomponent magma mixing.